A Database of Chinese-English Bilingual Speakers: Ratings of the Age of Acquisition and Familiarity - Wang, Jue; Chen, Baoguo (Frontiers in Psychology, 2020)
Recently, considerable attention has been given to the effect of the age of acquisition (AoA) on learning a second language (L2); however, the scarcity of L2 AoA ratings has limited advancements in this field. We presented the ratings of L2 AoA in late, unbalanced Chinese-English bilingual speakers and collected the familiarity of the L2 and the corresponding Chinese translations of English words. In addition, to promote the cross-language comparison and motivate the AoA research on Chinese two-character words, data on AoA, familiarity, and concreteness of the first language (L1) were also collected from Chinese native speakers. We first reported the reliability of each rated variable. Then, we described the validity by the following three steps: the distributions of each rated variable were described, the correlations between these variables were calculated, and regression analyses were run. The results showed that AoA, familiarity, and concreteness were all significant predictors of lexical decision times. The word database can be used by researchers who are interested in AoA, familiarity, and concreteness in both the L1 and L2 of late, unbalanced Chinese-English bilingual speakers. The full database is freely available for research purposes.